Mini-Incision Eyelidplasty in Single Eye to Correct Congenital Upper Eyelid Crease Asymmetry. Issue 7 (October 2021) - Ninghua, Liu; Aijuan, He; Dan, Wu; Nan, Song
Abstract : Objective: This study aims to evaluate the clinical effect of mini-incision double eyelidplasty in single eye for correcting congenital upper eyelid crease asymmetry. Methods: Mini-incision double eyelidplasty was performed on 24 patients in single eye to treat congenital upper eyelid crease asymmetry between May 2016 and September 2018. The postoperative surgical results were classified as "excellent, " "fair, " and "poor." The subjective satisfaction and incidence of complications were documented. Results: The mean patient age at the time of surgery was 24.6 ± 3.1 years (21–28 years), and the mean follow-up time was 15.4 ± 8.7 (12–34 months). All patients showed "excellent" surgical outcomes according to symmetry of upper eyelid creases. All patients are "very satisfied" with the cosmetic outcomes. There were no cases of recurrence or other complications. Conclusions: Mini-incision double eyelidplasty method in single eye was effective and endurable in the treatment of congenital upper eyelid crease asymmetry. The recovery rate was fast, and no cases of upper eyelid crease disappearance were observed in this study.